Avaliação teórico-experimental de peças estruturais de madeira, solicitadas a cargas de impacto, para uso em carrocerias - Everton Cruvinel Junior (2009)
Nowadays, models and criteria of calculation for components of the truck bodies do not exist. Moreover specific methodologies of assays and characterizations for this activity do not exist. Everything what was made on the subject is empirical. The approach of this work is to analyzestructural wooden parts for use, mainly in truck bodies, through the knowledge of its resistance to the impact. For this, was mounted a system to analyze importants structural components of truck body called crossbar or battens. The load application system was free falling weight. Weights had been untied of different heights initiating in zero up to 100 cm in multiples of 10 cm. The force was increased gradually, by the inclusion of nominal weights of 10 kg. The load was applied until reaching the rupture of each crossbar. Using 16 samples in real size (all of them Brazilian wooden species [Dinizia excelsa Ducke], [Eucalyptus grandis], [Peltogyne recifensis Ducke] e [Dipteryx odorata Willd]). All crossbars analyzed had been characterized in laboratory following the criteria of Brazilian standard (NBR 7190/97). After analysis of multiple linear regression, it was possible to get an equation with high degree ofsignificance (R2 = 93.47%) that correlates force of reaction in function of free falling heights, elasticity modulus and impact loads. It has proceeded to analyses of impact factors n which it has concluded that, for use in wooden crossbars, it must be adequated according to an equationpresented in this study. Comparing the experimental wood resistance with the values gotten through the characterization of the material, an average increase of 115% was verified when submitted to impact loads.